Evaluation of the Antimicrobial Efficacy of Hibiscus sabdariffa L. Antiperspirant Preparations Against Staphylococcus epidermidis - Dwisari, Fath; Dermawan, Abdurraafi Maududi; Amalia, Puspa; Tjoadri, Tessa Nathalia; Rahma, Nur Atika (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2025)
Commercial antiperspirant products commonly incorporate synthetic compounds, several of which have raised concerns due to their potential carcinogenicity. Moreover, the inclusion of natural antibacterial agents in these formulations remains limited. Hibiscus sabdariffa L. (Rosella), a plant rich in bioactive secondary metabolites, offers a promising natural alternative. This study aimed to evaluate the antibacterial efficacy of rosella-based antiperspirant formulations, particularly against Staphylococcus epidermidis, a key contributor to body odor. Three formulations (F1, F2, and F3) were developed and assessed based on several parameters: pH, organoleptic properties, homogeneity, spreadability, adhesiveness, and antibacterial activity against Staphylococcus epidermidis. The results demonstrated that the antiperspirant preparations complied with standard evaluation criteria. Furthermore, the antibacterial assay outcomes yielded statistically significant differences (p < 0.05) in the mean diameter of the inhibition zones, indicating that H. sabdariffa L. exhibited measurable antibacterial activity against S. epidermidis. These findings support the potential application of Rosella extract in developing natural and efficacious anti-perspirant products.